On technofeudalism: What killed capitalism? An interview with Yanis Varoufakis - Giannēs Baruphakēs; Michaēl S. Zumpulakēs (Economic Thought, 2023)
Yanis Varoufakis is an economist and politician. After serving as Greek Finance Minister in 2015, he went on to co-found the Democracy in Europe Movement 2025, of which he is now Secretary- General. The author of many books and academic papers, his latest work, Technofeudalism: What Killed Capitalism?, was published by Bodley Head in 2023. Professor of Economics, and editor of this journal, Michel Zouboulakis interviewed Varoufakis in December 2023. What follows is a transcript of that meeting.
Keywords: 330